Miriam's secret [large type] - Eicher, Jerry S. (Eicher, Jerry S. Land of promise, 2015)
Miriam Yoder has a secret. Her compassionate care for Amos Bland during his last days brought her a large inheritance. So when Ivan Mast indicates his intentions at romance, Miriam suspects he's discovered her hidden wealth. Seeking a fresh start where no one knows her, Miriam accepts a teaching position in faraway Oklahoma. There she meets Wayne Yutzy, whose interest in her seems genuine. Happiness surely awaits the couple . . . or does it?